Performance and cycling efficiency after supra-maximal interval training in trained cross-country mountain bikers - Gendron, P.; Dusfresne, P.; Laurencelle, L.; Trudeau, F.; Bergerion-Vaillancourt, S. (International Journal of Applied Sports Sciences, 2016)
The purpose was to examine improvements of performance and different physiological parameters in ten trained male cross-country mountain bikers after a supra-maximal interval training (SMIT) program of 8 sessions. Each session comprised 60 to 90 repeated 1-minute bouts consisting of a 20-s effort at 115% of maximal aerobic power (MAP), followed by 40-s recovery at 50% of MAP. Performance time to complete the virtual time-trial performance test was reduced significantly by -4.2%. Pulmonary sub-maximal oxygen consumption and deoxyhemoglobin in vastus lateralis decreased significantly by ?4.7% and -21.9% respectively during the MAP test. Our findings suggest that SMIT program might improve performance and cycling efficiency in XC mountain bikers.